Donald M. MURRAY. The craft of revision. Fifth Anniversary Edition. Boston: Wadsworth. Cengage Learning, 2013. xxi + 261pp. ISBN-13: 978-0-8400-2885-3 [Recensão] - Pinto, Maria da Graça L. Castro (Linguarum Arena, 2018)
.